Traumatic Brain Injury by Weight-Drop Method Causes Transient Amyloid-β Deposition and Acute Cognitive Deficits in Mice - Hajime Shishido; Masaki Ueno; Kana Sato; Masahisa Matsumura; Yasunori Toyota; Yutaka Kirino; Takashi Tamiya; Nobuyuki Kawai; Yasushi Kishimoto (Behavioural Neurology)
There has been growing awareness of the correlation between an episode of traumatic brain injury (TBI) and the development of Alzheimer’s disease (AD) later in life. It has been reported that TBI accelerated amyloid-β (Aβ) pathology and cognitive decline in the several lines of AD model mice. However, the short-term and long-term effects of TBI by the weight-drop method on amyloid-β pathology and cognitive performance are unclear in wild-type (WT) mice. Hence, we examined AD-related histopathological changes and cognitive impairment after TBI in wild-type C57BL6J mice. Five- to seven-month-old WT mice were subjected to either TBI by the weight-drop method or a sham treatment. Seven days after TBI, the WT mice exhibited significantly lower spatial learning than the sham-treated WT mice. However, 28 days after TBI, the cognitive impairment in the TBI-treated WT mice recovered. Correspondingly, while significant amyloid-β (Aβ) plaques and amyloid precursor protein (APP) accumulation were observed in the TBI-treated mouse hippocampus 7 days after TBI, the Aβ deposition was no longer apparent 28 days after TBI. Thus, TBI induced transient amyloid-β deposition and acute cognitive impairments in the WT mice. The present study suggests that the TBI could be a risk factor for acute cognitive impairment even when genetic and hereditary predispositions are not involved. The system might be useful for evaluating and developing a pharmacological treatment for the acute cognitive deficits.